ACCELERATIVE AND TRANSFORMATIVE: THE LEADERSHIP OF DEDI ISKANDAR BATUBARA IN STEERING AL-JAM’IYATUL WASHLIYAH IN NORTH SUMATRA - Devrichan Syahputra Zalukhu Zalukhu; Sukiman Sukiman; Mhd Syahminan (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the leadership model of Dedi Iskandar Batubara at the North Sumatra Regional Board of Al-Washliyah, characterized by an accelerative and transformative vision within the framework of Islamic political thought. Employing a qualitative case study methodology, data were collected through in-depth interviews with the research subject and key informants. The findings indicate that Batubara’s leadership is grounded in a spiritual philosophy that construes his position as a sacred trust (amanah) and an act of worship (ibadah), compelling him to drive innovation and systematic improvements. His leadership model is democratic, transparent, and humanistic, consistently implementing Islamic political principles such as consultation (syura) and trustworthiness (amanah) in all decision-making and organizational management processes. He has also successfully addressed internal challenges, including political diversity and intergenerational dynamics, by upholding the principle of independence and prioritizing cadre regeneration. This accelerative and transformative vision has not only yielded significant advancements in the fields of Islamic propagation (da’wah), education, and asset management but has also enhanced Al-Washliyah’s public credibility. This study concludes that Dedi Iskandar Batubara’s leadership exemplifies an effective model of how a leader can balance Islamic idealism with the demands of modernity to ensure the organization’s sustainability and relevance in the contemporary era.